2020
DOI: 10.1182/bloodadvances.2020003238
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage with direct oral anticoagulants in patients with brain metastases

Abstract: Direct oral anticoagulants (DOACs) are increasingly prescribed in treatment of cancer-associated thrombosis, but limited data exist regarding safety of DOACs in patients with brain metastases. We aimed to determine the incidence of intracranial hemorrhage (ICH) in patients with brain metastases receiving DOACs or low-molecular-weight heparin (LMWH) for venous thromboembolism or atrial fibrillation. An international 2-center retrospective cohort study was designed. Follow-up started on the first day of concomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The incidence of any ICH among patients with brain tumors is high but does not appear to be influenced by the administration of anticoagulants. 4,[7][8][9]24,25 Similar data on the safety of aspirin in patients with brain metastases is lacking. In this matched cohort study of nearly 400 patients with blinded radiology review of ICH, the administration of antiplatelet therapy was not associated with an increase in the incidence, size, or severity of ICH in the setting of brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of any ICH among patients with brain tumors is high but does not appear to be influenced by the administration of anticoagulants. 4,[7][8][9]24,25 Similar data on the safety of aspirin in patients with brain metastases is lacking. In this matched cohort study of nearly 400 patients with blinded radiology review of ICH, the administration of antiplatelet therapy was not associated with an increase in the incidence, size, or severity of ICH in the setting of brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an international two-center study suggested comparable safety of LMWH and DOACs in patients with brain metastases. The 12-month cumulative incidence of major ICH was 5.1% in DOAC-treated patients and 11.1% in those treated with LMWH (HR: 0.45; 95% CI 0.09 to 2.21) [ 46 ]. When anticoagulation was analyzed as a time-varying covariate, the risk of any ICH did not differ between DOAC- and LMWH-treated patients (HR: 0.98; 95% CI 0.28 to 3.40) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 12-month cumulative incidence of major ICH was 5.1% in DOAC-treated patients and 11.1% in those treated with LMWH (HR: 0.45; 95% CI 0.09 to 2.21) [ 46 ]. When anticoagulation was analyzed as a time-varying covariate, the risk of any ICH did not differ between DOAC- and LMWH-treated patients (HR: 0.98; 95% CI 0.28 to 3.40) [ 46 ]. Finally, a single-center retrospective chart review of 125 patients with primary and metastatic brain tumors on anticoagulation reported rates of major bleeding of 26% and 9.6% in patients receiving LMWH or DOAC, respectively [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of studies evaluating the risk of ICH in patients with brain metastases receiving anticoagulation, therapeutic doses of LMWH did not increase the risk of ICH compared with no anticoagulation (OR 1.07, 95% CI 0.61-1.88) [35]. Finally, a retrospective cohort of patients with brain metastases receiving anticoagulation found that the cumulative incidence of ICH at 12 months did not differ between patients treated with DOAC and those treated with LMWH (5.1% vs.11.1%, HR 0.45, 95% CI 0.09-2.21) [36].…”
Section: Cancer Site and Stagementioning
confidence: 97%